Corynebacterium ulcerans cutaneous diphtheria. Issue 9 (September 2015) - Moore, Luke S P; Leslie, Asuka; Meltzer, Margie; Sandison, Ann; Efstratiou, Androulla; Sriskandan, Shiranee
Summary We describe the case of a patient with cutaneous diphtheria caused by toxigenic Corynebacterium ulcerans who developed a right hand flexor sheath infection and symptoms of sepsis such as fever, tachycardia, and elevated C-reactive protein, after contact with domestic cats and dogs, and a fox. We summarise the epidemiology, clinical presentation, microbiology, diagnosis, therapy, and public health aspects of this disease, with emphasis on improving recognition. In many European countries, C ulcerans has become the organism commonly associated with cutaneous diphtheria, usually seen as an imported tropical disease or resulting from contact with domestic and agricultural animals. Diagnosis relies on bacterial culture and confirmation of toxin production, with management requiring appropriate antimicrobial therapy and prompt administration of antitoxin, if necessary. Early diagnosis is essential for implementation of control measures and clear guidelines are needed to assist clinicians in managing clinical diphtheria. This case was a catalyst to the redrafting of the 2014 national UK interim guidelines for the public health management of diphtheria, released as final guidelines in March, 2015.